Students’ Perception on Using Electronic Module Learning Material in Distance Learning: Presented by an Asynchronous - Satriani, Estika; Idayani, Andi; Kadar, Destry Pryanti (Universitas Lancang Kuning, 2024)
The world of education is currently experiencing a transformation in the learning process which allows the implementation of distance learning. Therefore, learning media is needed to facilitate students in the distance learning process, one of which is using e-module learning materials presented using an asynchronous method. This research aims to determine students' perceptions regarding electronic modules (e-modules) as a distance learning media using asynchronous methods. Four things are measured in knowing student perceptions regarding the electronics module (e-module), namely the clarity and suitability of text, images, and animations in the e-module, the presentation of learning material in the e-module, the usefulness of the e-module, and ease of access. Research data was collected using a questionnaire that was filled out online by students using Google Forms. The populations in this study were students from the 2023 class of the FKIP-UIR English Language Education, with a total of 65 students who were also the samples in this study. The data was analyzed using data verification steps, scoring, calculating the percentage of each answer category, and displaying the data in table form. Then the researcher interprets the results of the data analysis. The research results show that the average overall student perception results are 96% in the positive category. This indicates that the electronic module (e-module) for the Intensive Reading course is suitable for use as a distance learning media using an asynchronous method. The implication of research, the study can be used for other learning course and other method.